Variant selection during β to α transformation for Ti-6Al-4V alloy produced by Selective Laser Melting printing. Issue 1 (March 2021) - Xiang, H.; Kestens, L.A.I.; Van Paepegem, W.
Abstract: During 3D printing by Selective Laser Melting (SLM) of the alloy Ti-6Al-4V, the phase transformation of BCC to HCP is associated with selection of particular crystallographic variants. In the present paper, the distribution of misorientation angle along grain boundaries was investigated by EBSd. It is revealed that the main misorientation pairs were located in the interval between 56° and 66°, which contains three theoretical misorientation angles, i.e. 60.00°, 60.83° and 63.26°. The observed misorientation axis/angle pairs were represented in the Rodrigues–Frank space with a certain tolerance angle, which illustrated clearly the distribution of the observed misorientations around the 5 theoretical values. The main peak of the misorientation pairs was observed for [ 10 5 5 3 ] / 63.26 ° with 43.8% frequency, followed by 1 2 0 ] / 60 ° with 21.8% population, whereas a distribution in the absence of variant selection would have produced values of 18.2% and 36.4%, respectively.